2015
DOI: 10.1093/infdis/jiv480
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Humoral Responses to a Second Dose of Herpes Zoster Vaccine Administered 10 Years After the First Dose Among Older Adults

Abstract: NCT01245751.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
48
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 28 publications
3
48
1
Order By: Relevance
“…However, a booster dose has potential to reverse this decline in protection. A clinical trial found a booster dose of Zostavax, given ≥10 years after the first dose among adults ≥70 years, elicited a VZV antibody response similar to that of a first dose among age-matched subjects [113]. This booster dose was safe and some initial modeling work suggests such a vaccination strategy would be cost effective [101].…”
Section: Zoster Vaccine – Unresolved Questionsmentioning
confidence: 99%
“…However, a booster dose has potential to reverse this decline in protection. A clinical trial found a booster dose of Zostavax, given ≥10 years after the first dose among adults ≥70 years, elicited a VZV antibody response similar to that of a first dose among age-matched subjects [113]. This booster dose was safe and some initial modeling work suggests such a vaccination strategy would be cost effective [101].…”
Section: Zoster Vaccine – Unresolved Questionsmentioning
confidence: 99%
“…A recently published study reported fairly robust cellmediated immune responses after a booster dose in persons who had received an initial HZ vaccine 10 years earlier. 4 The potential clinical benefit of a booster should be weighed against its added cost.In this issue of the Journal of General Internal Medicine, Le and Rothberg report a methodologically robust and well-timed cost-effectiveness analysis which sought to determine the optimal schedule for the live attenuated HZ vaccine.5 This work builds upon their previously published and guidelinecited cost-effectiveness analysis of HZ vaccination. 1,6 The authors updated their well-developed Markov model, newly incorporated data regarding the long-term efficacy of the vaccine, and evaluated strategies entailing booster doses.…”
mentioning
confidence: 99%
“…Recent data have suggested that a booster might induce greater immunity than an initial dose in persons ≥70 years old. 4 We anxiously await reports of the clinical short-term and …”
mentioning
confidence: 99%
See 2 more Smart Citations